Satisfaction, inertia, and customer loyalty in the varying levels of the zone of tolerance and alternative attractiveness - Wu, Li-Wei (The Journal of services marketing, 2011)
Purpose - Empirical studies investigating the antecedents of customer loyalty typically focus on satisfaction. This study aims to develop and test a more comprehensive model of the antecedents of customer loyalty, including satisfaction and inertia. In addition, this study also considers how the effects of satisfaction and inertia on customer loyalty vary with differing levels of the zone of tolerance (ZOT), and how these are likely to change due to customers' alternative attractiveness.Design methodology approach - Hierarchical moderated regression analysis was used to test the hypotheses.Findings - The results show that a wider level of the ZOT strengthens the positive effect of inertia on customer loyalty, while also reducing the positive effect of satisfaction. The results also indicate that the negative moderating effect of the ZOT on the relationship between satisfaction and customer loyalty will reduce as alternative attractiveness increases. In contrast, the positive moderating effect of the ZOT on the relationship between inertia and customer loyalty will reduce as alternative attractiveness increases.Originality value - This study is a first attempt to integrate the ZOT to determine the relative importance of satisfaction and inertia in determining customer loyalty. In addition, this study suggests that customers with higher perceptions of alternative attractiveness are more likely to experience changes in the influence of the ZOT on their loyalty decisions.